Hukum Penghasilan Professional Player E-Sports Mobile Legends dalam Tinjauan Fikih Muamalah - Musyirul Haq; Khaerul Aqbar; Dzul Fadli S. (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to analyze the legal status of the income of a professional Mobile Legends e-sports player from the perspective of Islamic jurisprudence (fiqh muamalah). This research employs a library research method, which falls under qualitative research, using a normative approach that examines primary and secondary legal materials. Primary data includes Islamic legal sources such as the Qur'an and Hadith, while secondary data includes the opinions of scholars, relevant literature, and previous research findings. The results of the study indicate that earning income from tournament victory bonuses for a professional Mobile Legends e-sports player is halal (permissible) as the essential elements and conditions are fulfilled. However, this profession is not recommended for a Muslim due to its lack of benefits for oneself and others. This conclusion is based on an analysis of the principles of fiqh muamalah, which emphasize the conformity of economic activities with Islamic values and ethics. This study makes a significant contribution by providing insights into the compatibility of modern gaming professions with Islamic muamalah ethics, which is expected to serve as a guide for Muslim professional e-sports athletes in conducting e-sports activities in accordance with Islamic teachings. It also offers valuable input for stakeholders in the e-sports industry to consider Islamic legal aspects in the organization of tournaments and prize distribution. Thus, this research not only provides practical guidance for professional players but also opens further discussion for subsequent researchers to explore deeper into the law and ethics of various aspects of modern gaming from an Islamic perspective.